Expression of EGFR family and p53 in a patient with Synchronous Primary Endometrial Adenocarcinoma and Clear Cell Renal Carcinoma: a Case Report - Priscila Fernanda da Silva Martins; Izabella Cristina Alves Souza; Enio Ferreira; Emerson Soares Veloso; Tatiany L Silveira; Adam Underwood; Fabiano Conde Araujo; Helen Lima Del-Puerto (Brazilian Journal of Oncology)
We present a case of a 69 year-old, non-obese, post-menopausal woman diagnosed with synchronous endometrial adenocarcinoma and renal cell carcinoma. Immunolocalization and expression of the EGFR, HER-2, HER-3, HER-4 and p53 proteins by immunohistochemistry (IHC) was performed to investigate synchronous expression of these proteins. The endometrial adenocarcinoma was a well-differentiated tumor, with discernable glandular structure with moderate mitotic index. IHC revealed weak HER-2, HER-3 and HER-4 staining of cell membranes in well-differentiated areas, and intense HER-2 and p53 staining in papillary areas. The renal cell carcinoma showed clear cell type, solid tumor, Fuhrman nuclear grade 2, presence of necrosis and hemorrhage. IHC revealed intense HER-2 and HER-4 staining of cell membranes, weak EGFR staining, and negative expression for HER3 and p53 protein. In summary, overexpression of HER-2 and HER-4 may correlate with histological grade of the tumor and patient prognosis.